2022
DOI: 10.18632/aging.204207
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of BCL-2 family inhibitors facilitates selective elimination of senescent cells

Abstract: Accumulation of senescent cells in tissues with advancing age participates in the pathogenesis of several human age-associated diseases. Specific senescent secretome, the resistance of senescent cells to apoptotic stimuli, and lack of immune system response contribute to the accumulation of senescent cells and their adverse effects in tissues. Inhibition of antiapoptotic machinery, augmented in senescent cells, by BCL-2 protein family inhibitors represents a promising approach to eliminate senescent cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Senescence of senescent cells or telomere attrition is an important cause of senescence, and therefore, anti-aging strategies by scavenging senescent cells and reducing the attrition of telomeres are also potential pharmacological strategies. 30,31 Current research suggests that aging is primarily associated with nutrient sensing disorders, mitochondrial dysfunction, and cellular senescence, 23 but there are many questions about how to reverse or delay aging, which needs to be further explored.…”
Section: Aging and Anti-aging Therapymentioning
confidence: 99%
“…Senescence of senescent cells or telomere attrition is an important cause of senescence, and therefore, anti-aging strategies by scavenging senescent cells and reducing the attrition of telomeres are also potential pharmacological strategies. 30,31 Current research suggests that aging is primarily associated with nutrient sensing disorders, mitochondrial dysfunction, and cellular senescence, 23 but there are many questions about how to reverse or delay aging, which needs to be further explored.…”
Section: Aging and Anti-aging Therapymentioning
confidence: 99%
“…Since TIS involves the increased expression of BCL-2, targeting BCL-2 may exert anticancer effects. BCL2-targeting drugs, including ABT-737 and ABT-263 (navitoclax), natural substances, such as artesunate, fisetin, and curcumin, showed senolytic effects in glioblastoma cells and non-transformed cells [ 83 , 167 ]. ABT-263 eliminated senescent cells and enhanced the efficacy of olaparib, a PARP inhibitor, in both breast and ovarian cancer cell lines [ 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells emerging from senescence display higher anticancer drug resistance than cancer cells without senescence [ 46 ]. Senescent cells display resistance to apoptosis owing to high level of BCL-2 [ 83 ], suggesting the role of senescence in therapeutic resistance. Lapatinib and fulvestrant (EGFR and HER2 inhibitors) treatment induced apoptosis in chemotherapy-induced senescent breast cancer cells [ 84 ].…”
Section: Roles Of Sasp In Cancer Cell Proliferation and Therapeutic R...mentioning
confidence: 99%
See 1 more Smart Citation
“…our previous studies demonstrated that tumour growth of proliferating murine Tc-1 HPV-16-associated cancer cells in syngeneic mice was accelerated by co-administration of Tc-1 or TraMP-c2 cancer cells that were made senescent by pre-treatment with the anti-cancer agent docetaxel (dTX) (22). dTX was also successfully used for the induction of senescence in human cell lines (23). These studies suggested that dTX-treated cells can be a useful model for studies focused on senescent cells.…”
Section: Stat3 Inhibitor Stattic and Its Analogues Inhibit Stat3 Phos...mentioning
confidence: 99%